Análise multiatributos de AVO para discriminação de fácies carbonáticas - Contreras, Candy Shirley Rosa (2018)
The Brazilian Albian carbonate reservoirs are good producers of hydrocarbons, especially in the southern part of the Santos Basin, which has fields discovered more than 30 years ago. However, carbonate reservoirs are a challenge for seismic interpreters because of the heterogeneity of the pores associated with the complicated formation process, which leads to a decrease in the understanding of the relationship between the petrophysical properties of the carbonates and their seismic response. In order to characterize the Albian carbonate reservoirs of the Guarujá Formation belonging to Estrela do Mar Field in the southern portion of the Santos Basin, the amplitude versus offset (AVO) method and the rock physics model were used. Thus, a seismic processing flow with preservation of amplitude was applied in a 2D pre-stack seismic data for generating migrated gathers. This data after calibration was used to define a set of AVO attributes correlated with petrophysical properties. These attributes together with AVO crossplot analysis allowed us to make a qualitative interpretation of the carbonate reservoirs. The study of the rock physics model is used to understand the porous system of the carbonate rocks and to investigate the effect of the fluids in the seismic responses.